Determinantes da apreciação da interpretação musical: hábitos de escuta, escolaridade e área de formação acadêmica - Leme Junior, Antonio Carlos (Universidade Federal de São Carlos, 2014)
Musical knowledge, although usually conceived as instrumental expertise, has another important element: appreciation. Whereas most people can listen to musical stimuli, the way these stimuli are appreciated is largely influenced by individuals learning history. This study investigates how people with different learning histories concerning musical experience appreciate three performances of the same musical work recorded by performers of contrasting levels of expertise. To achieve this, three excerpts of a piano musical work were submitted to the appreciation of participants with discrepant levels of involvement with music (n=79). Participants task consisted of evaluate how much they liked each performance using a 7 point scale. The scores attributed to each performance were comparatively analyzed according to the educational level, listening habits and field of expertise of participants. Results point out that 1)the educational level of participants, as well as their field of expertise, correlates with the ability to discriminate between the performances presented and 2)in the case of non-amateur performances, the specific training of a musical instrument proved to be more decisive than other kinds of musical knowledge in order to help listeners to identify what is considered by musical community as a high level performance.
Determinants of performance-oriented music appreciation: music listening habits, educational level and field of expertise
Keywords: Música - aspectos psicológicos; Música - interpretação (Fraseado, dinâmica, etc.); Música - análise, apreciação; Música - aprendizagem; Music; Performance; Appreciation; Learning; CIENCIAS HUMANAS::PSICOLOGIA